2008
DOI: 10.1186/1471-2202-9-s1-p58
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the interaction of transcranial magnetic stimulation with a model cortical neuron

Abstract: IntroductionTranscranial magnetic stimulation (TMS) is a noninvasive technique that induces neuronal discharge in response to a rapidly changing magnetic field (B-field) directed through the scalp. However, the interaction between cortical tissue and the electric field (E-field) induced by the changing B-field remains unclear. A realistic multi-compartment model of a layer V pyramidal neuron receiving a simulated TMS pulse provides a means to characterize the influence of numerous parameters on cell discharge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We have previously reported that spiking is induced only when the primary electric (E) field is oriented from the soma toward the apical dendrite (antidromic stimulus). In contrast, an E-field oriented in the opposite direction from the apical dendrite toward the soma (orthodromic stimulus) evokes an excitatory potential (EP) considerably larger (3 mV) than that of an excitatory postsynaptic potential (about 0.75 mV at -70 mV resting potential in this system) [ 4 ]. The EP is not sufficient to induce cell firing [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that spiking is induced only when the primary electric (E) field is oriented from the soma toward the apical dendrite (antidromic stimulus). In contrast, an E-field oriented in the opposite direction from the apical dendrite toward the soma (orthodromic stimulus) evokes an excitatory potential (EP) considerably larger (3 mV) than that of an excitatory postsynaptic potential (about 0.75 mV at -70 mV resting potential in this system) [ 4 ]. The EP is not sufficient to induce cell firing [ 4 ].…”
mentioning
confidence: 99%
“…In contrast, an E-field oriented in the opposite direction from the apical dendrite toward the soma (orthodromic stimulus) evokes an excitatory potential (EP) considerably larger (3 mV) than that of an excitatory postsynaptic potential (about 0.75 mV at -70 mV resting potential in this system) [ 4 ]. The EP is not sufficient to induce cell firing [ 4 ]. To better understand this behavior, we explored the passive membrane response of the model system to different stimulus magnitudes.…”
mentioning
confidence: 99%